Crystal structure of bovine angiogenin at 1.5-A resolution. - Acharya, K R (1995)
The capacity of angiogenin (Ang) to induce blood vessel growth is critically dependent on its ribonucleolytic activity. Crystallography and mutagenesis of human Ang have previously shown that its pyrimidine binding site is obstructed by Gln-117, implying that a conformational change is a key part of the mechanism of Ang action. The 1.5-A-resolution crystal structure of bovine Ang, in which glutamic acid is substituted for Gln-117, now confirms that a blocked active site is characteristic of these proteins. Indeed, the inactive conformation of bovine Ang is stabilized by a more extensive set of interactions than is that of human Ang. The three-dimensional structure of the putative receptor binding site is also well conserved in the two proteins. The Arg-Gly-Asp segment of this site in bovine Ang, which is replaced by Arg-Glu-Asn in human Ang, does not have a conformation typical of an integrin recognition site.